Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
A parabola passes through the three points......?
A parabola passes through the three points (-1,1),(1,-2), and (4,1). Find the x intercepts and the vertex of the parabola
parabola equation is y=ax^2+bx+c
3 Answers
- NorthstarLv 71 decade agoFavorite Answer
The equation of the parabola is:
ax² + bx + c = y
Plug in the three points and get three equations.
a - b + c = 1
a + b + c = -2
16a + 4b + c = 1
Subtract the first equation from the second.
2b = -3
b = -3/2
Plug the value for b back in the second and third equations.
a + c = -1/2
16a + c = 7
Subtract the first equation from the second.
15a = 15/2
a = 1/2
Solve for c.
1/2 + c = -1/2
c = -1
The equation of the parabola is:
y = (1/2)x² - (3/2)x - 1
Solve for the vertex of the parabola.
y + 1 = (1/2)(x² - 3x)
y + 1 + (1/2)(9/4) = (1/2)(x² - 3x + 9/4)
y + 17/8 = (1/2)(x - 3/2)²
The vertex is (h,k) = (3/2, -17/8).
Solve for the zeros of the parabola.
(1/2)x² - (3/2)x - 1 = 0
x² - 3x - 2 = 0
x = {3 ± √[(-3)² + 4*1*(-2)]} / 2 = {3 ± √[9 + 8]} / 2 = (3 ± √17) / 2
The zeros are:
x = (3 ± √17) / 2
- 1 decade ago
y = ax^2 + bx + c
Substitute every point into the equation:
1 = a - b + c...........(1)
-2 = a + b + c.........(2)
1 = 16a + 4b + c.....(3)
Use equation 2 minus equation 1:
2b = -2-1
2b = -3
b = -3/2
Use equation 3 minus equation 1:
15a + 5b = 0
3a + b = 0
3a + (-3/2) = 0
3a = 3/2
a = 1/2
Substitute a = 1/2 and b = -3/2 into equation 1
1 = 1/2 - (-3/2) + c
c = -1
Therefore, y = 1/2 x^2 - 3/2 x - 1
When y = 0,
1/2 x^2 - 3/2 x - 1 = 0
x^2 - 3x - 2 = 0
x = (3 + Sqrt 17) / 2 or (3 - Sqrt 17) / 2
The answer of x is same as x-intercepts.
To find vertex, we need to do complement squares
1/2 x^2 - 3/2 x - 1
= 1/2 (x^2 - 3 x) - 1
= 1/2 [ (x - 3/2)^2 - 9/4 ] - 1
= 1/2 (x - 3/2)^2 - (1/2)(9/4) - 1
= 1/2 (x - 3/2)^2 - 9/8 - 1
= 1/2 (x - 3/2)^2 - 17/8
The vertex is (3/2, -17/8)
It is the minimum point
- Moise GunenLv 71 decade ago
plug x and y in y=ax^2+bx+c
You get
a-b+c=1
a+b+c = -2
16a+4b+c=1
subtract the second from first
-2b = 3 then b = -3/2
substitute in the third
16a-6+c=1
16a+c = 7
a+c = -1/2
15a = 15/2
a = 1/2
b = -3/2
c = -1
f(x) = (1/2)x^2-(3/2)x-1